1996
DOI: 10.1002/(sici)1097-4679(199603)52:2<125::aid-jclp2>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of coping in mental disorders: A prospective study in psychiatric outpatients

Abstract: The present follow-up study investigated the differential effects of dispositional coping styles on change in nine clinical syndromes of the Axis I spectrum of the DSM-III-R. Subjects were 155 psychiatric outpatients who were examined 6 and 7 years after their enrollment in the study. Coping accounted for up to 9% of the variance of symptom change over 1 year. As hypothesized, the effects of different coping styles varied considerably across the clinical syndromes. Active goal-oriented coping improved symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(18 citation statements)
references
References 57 publications
1
15
0
2
Order By: Relevance
“…Over and above this, we would like to suggest that the role of coping in the transactional model of stress should be reconsidered. In line with other studies, this study has shown that negative effects of coping are more important than positive effects (Aldwin & Revenson, 1987;Carver & Scheier, 1994;Vollrath et al, 1996). However, just how these negative effects translate into symptoms of mental disorders is not known.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Over and above this, we would like to suggest that the role of coping in the transactional model of stress should be reconsidered. In line with other studies, this study has shown that negative effects of coping are more important than positive effects (Aldwin & Revenson, 1987;Carver & Scheier, 1994;Vollrath et al, 1996). However, just how these negative effects translate into symptoms of mental disorders is not known.…”
Section: Discussionsupporting
confidence: 87%
“…This has been amply documented in prospective studies. In particular, poor use of problem-focused coping and reliance on avoidance coping leads to a deterioration of mental health in response to stress (Aldwin & Revenson, 1987;Aspinwall & Taylor, 1992;Bolger, 1990;Bolger & Zuckerman, 1995;Carver et al, 1993;Carver & Scheier, 1994;Felton & Revenson, 1984;Hoffart & Martinsen, 1993;Holahan & Moos, 1991;Kleinke, 1992;Vollrath et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inmates of this group, by using comparatively more approach than avoidance coping, should have benefited from the supposed protective effects of this type of coping, but the results did not confirm this argument. In fact, there are prospective studies that report an increase of anxiety and threatening feelings, together with the use of problem‐focused strategies (Aldwin & Revenson, 1987; Vollrath, Alnaes & Torgersen, 2003). We suggest that perhaps the very situation of imprisonment, with its great limitations on freedom of performance, makes it difficult to put into practice those approach strategies directed toward the solution of problems, and therefore the subject ends up demoralized.…”
Section: Discussionmentioning
confidence: 99%
“…22 We expected an interaction between active coping and both types of health, 20,23 because similar outcomes of coping were found for both mental and physical disorders. [24][25][26][27][28][29] In summary, for both mental and physical health, we hypothesized that negative effects of physical and mental health problems on work ability would be strongest for persons using an avoidant coping style and weakest for those using an active coping style and those seeking social support. This study was designed to address the following research questions:…”
mentioning
confidence: 99%